2021
DOI: 10.3390/jmse9121400
|View full text |Cite
|
Sign up to set email alerts
|

Basic Principles (Indicators) for Assessing the Technical and Economic Potential of Developing Arctic Offshore Oil and Gas Fields

Abstract: Sustainable development of the Arctic is the main priority of the state policy regarding regional development of the Russian Federation. The study of the Arctic zone of the Russian Federation for the formation of principles, methods and strategies, as well as organizational and economic mechanisms for its sustainable development is topical at present. This article deals with one of the strategic decision-making tools used in the process of implementing the development program for the Russian Arctic, namely, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Many studies have focused on the issues of sustainable development in the Arctic [3][4][5]86,87,[98][99][100][101][102][103][104][105]. However, it is not possible to define a single system of measures allowing to move away from the resource and raw material model.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the issues of sustainable development in the Arctic [3][4][5]86,87,[98][99][100][101][102][103][104][105]. However, it is not possible to define a single system of measures allowing to move away from the resource and raw material model.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the literature on the research subject revealed that there are several fullfeatured products capable of monitoring gas concentration [91][92][93]. The advantages of such developments are a large number of monitoring functions.…”
Section: Delay (2000); }mentioning
confidence: 99%
“…Therefore, the establishment of effective waste-management systems that transform waste into valuable resources and materials is an important step towards fostering a circular economy [6]. Nevertheless, the adoption of such waste-management practices in developing countries remains improbable due to limited funding, inadequate government incentives, technological shortcomings, and regulatory deficiencies [7,8].…”
Section: Introductionmentioning
confidence: 99%